2022
DOI: 10.21448/ijsm.1075283
|View full text |Cite
|
Sign up to set email alerts
|

A research paper on the immunomodulatory and anti-inflammatory activities of olive tree (Olea europaea L.) leaf

Abstract: Olive tree (Olea europaea L.) leaf is known to have a number of bioactive properties being antioxidant, antihypertensive, antiatherogenic, anti-inflammatory, antifungal, antiviral and antimicrobial. In this study, the immunomodulatory roles of Olive tree (Olea europaea L.) leaf against oxidative damage caused by carbon tetrachloride (CCl4) in Saccharomyces cerevisiae were investigated. In the study, four groups were formed; namely, (i) Control Group: Yeast only planted group; (ii) CCl4 Group: Group given CCl4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…It has been demonstrated that luteolin-7-O-glucoside could have gastroprotective effects in animal models of gastric ulcers [ 16 ]. Certainly, O. europaea leaf extract could have a pleiotropic effect mainly attributed either to the total phenols or to the individual phenolic compounds and to flavonoids and their derivatives, that have powerful antioxidant and anti-inflammatory activities in culture cells [ 17 ], invertebrates [ 18 ] and mammals [ 19 , 20 ]. In traditional herbal medicine, O. europaea leaves have been extensively used to reduce blood sugar, cholesterol, uric acid, diarrhoea, respiratory and urinary tract infections and gastro-intestinal diseases [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that luteolin-7-O-glucoside could have gastroprotective effects in animal models of gastric ulcers [ 16 ]. Certainly, O. europaea leaf extract could have a pleiotropic effect mainly attributed either to the total phenols or to the individual phenolic compounds and to flavonoids and their derivatives, that have powerful antioxidant and anti-inflammatory activities in culture cells [ 17 ], invertebrates [ 18 ] and mammals [ 19 , 20 ]. In traditional herbal medicine, O. europaea leaves have been extensively used to reduce blood sugar, cholesterol, uric acid, diarrhoea, respiratory and urinary tract infections and gastro-intestinal diseases [ 21 ].…”
Section: Introductionmentioning
confidence: 99%